Design of a modular Fortran 90 molecular mechanics package for hydrocarbons - Shaw, Michelle, 1975- (2000)
Thesis (M.Sc.)--Memorial University of Newfoundland, 2000. Computational Science Bibliography: leaves 146-152 Molecular mechanics is a popular method for minimization of energies of large biomolecular structures and much work has been done in creating packages which optimize the execution time and memory requirements. Object-based design is a useful tool in creating packages which are easily updated and clearer than procedural- based design due to their inherent modularity. The current codes in use are Fortran 77 and C, but Fortran 90 may prove to be a more viable option for object-based molecular mechanics. In this work, a molecular mechanics package based on the Merck Molecular Force Field (MMFF94) is designed for hydrocarbons using existing Fortran 90 tools and object-based design techniques. Presented in this work are the analysis, design, and implementation of the molecular mechanics package as well as a report of the numerical results. Included in the numerical results are comparisons with literature values for the conformational differences for the ethane and cyclohexane systems.